Microstates in world affairs : policy problems and options - Plischke, Elmer; American Enterprise Institute for Public Policy Research (Washington D. C. : American Enterprise Institute for Public Policy Research, 1977)
This book provides a comprehensive analysis of the expansion of the global community and its possible and probable future growth.
Includes bibliographical references.
oo 22/01/2019
Loans
Keywords: International relations; Underdeveloped areas---Foreign relations; Developing countries